Do trade barriers and financial freedom matter in becoming a rich country? - Ang, Joshua; Patalinghug, Jason (Journal of Business and Economic Studies, 2026)
A lot has been written on the impact of economic freedom and its components on economic growth. This paper focuses on financial freedom, which is one aspect of economic freedom. Financial freedom measures how deeply the government is involved in a nation’s financial industry and how that industry is open to foreign competition. The aim of this study is to measure the effect of financial freedom and other factors on gross domestic product (GDP) per capita. We estimate a model using panel data of 184 countries from 2012 to 2019. Our empirical estimations show that financial freedom positively affects per capita GDP, while tariff rates, corporate tax rates, unemployment, and inflation negatively affect per capita GDP.
Keywords: Economic freedom; Financial analysis; Government (linguistics); Gross domestic product; Index of Economic Freedom; Inflation (cosmology); Panel data; Per capita; Tariff; dept.eco

Financial innovation, gender, and credit access: evidence from Ghanaian microenterprises - Thorson, J.A.; Andoh, S. (International Conference on Business Research, 2025)
Keywords: Cash; Closing (real estate); FinTech; Financial inclusion; Financial services; Financial transaction; Mobile banking; Mobile payment; Savings account; dept.eco

Joining farmers’ cooperatives leads to equitable poverty reduction in China – empirical evidence from the rural households survey - Zhang, Ze; Qin, Lijian; Jia, Yu; Li, Yuheng; Hong, Chen; Qin, Wenshuai (Applied Economics, 2025)
Keywords: China; Empirical evidence; Inequality; Poverty; Poverty reduction; Rural poverty; Survey data collection; dept.eco

Will social participation make retirees happier? An empirical study about retirement life in China - Zhao, Luman; Yu, Jia (Journal of Applied Business and Economics, 2025)
How elderlies participate in social activities is a key issue in coping with aging and has an important impact on elderlies’ well-being. This paper examines the effects of different social participation patterns on the happiness of the elderlies in China. The empirical analysis was conducted based on the data from the China Household Finance Survey (CHFS) in 2015. The research results show that compared with reemployment after retirement, community governance is a more common way for retired people to be involved in social activities. We found that reemployment significantly reduces the happiness degree of the retired. Furthermore, this negative effect is more significant in samples without a formal labor contract, relatively lower education level, & senior retired people. In contrast, participating in community governance can significantly improve the happiness level of retirees, which is more essential in the sample of the medium education level and junior retirees.
Keywords: Business; China; Demographic economics; Economics; Empirical research; Labour economics; Life satisfaction; Political science; Psychology; Social psychology; dept.eco

Some determinants of income inequality in Asia and Latin America - Patalinghug, Jason (Valahian Journal of Economic Studies, 2025)
Abstract Income inequality has, in recent years, become a serious issue especially in emerging markets. This paper examines the relationship of income inequality in the Asia-Pacific and Latin America regions to several factors such as gross capital formation, corruption, and per capita gross domestic product (GDP). Using a cross-sectional dataset of 36 countries from both regions for the year 2018 and ordinary least squares regression, the paper shows that gross capital formation and the lack of corruption have a negative and significant relationship with income inequality (as represented by the Gini coefficient). In contrast, per capita GDP has a positive and significant relationship with income inequality. Policymakers who want to rein in income inequality should therefore focus on ways to reduce corruption and increase the formation of capital. This study could be of use for those who are interested in discovering and mitigating the factors that cause income inequality in the developing world.
Keywords: Business; Business informatics; Business management; Demographic economics; Development economics; Economic growth; Economic inequality; Economics; Health care; Income distribution; Inequality; Latin Americans; Mathematics; Political science; dept.eco

Testing for Consistency in Firm Entry and Exit Between the National Establishment Time Series and Business Dynamics Statistics - Kim, Donghyuk; Kim, Younjun; Orazem, Peter; Thomas, Kelsey (Growth and Change, 2026)
Keywords: Business statistics; Census; Consistency (knowledge bases); Dynamics (music); Longitudinal data; Series (stratigraphy); Time series; dept.eco; entrepreneurship; entry; exit; firm data

Bilateral environmental aid under trade competition - Yoon, Sang; Kim, Younjun; Park, Byoung; Yoon, Chang-Ho (Applied Economics Letters, 2026)
Keywords: Bilateral environmental aid; Bilateral trade; Competition (biology); Environmental impact assessment; Environmental policy; Trade barrier; climate finance; dept.eco; energy-saving aid; strategic aid allocation; trade competition

Green banking: prospects and challenges - D'Amora, Emily C.; Andoh, Samuel K (Southwest Business and Economics Journal, 2025)
The paper examines the concept of green banking and sustainable financing, the forces driving green banking, and the reasons for this. The paper suggests that the move toward green banking and financing is the result of environmental degradation and the public’s demand for remediation. As enablers of the industries that create pollution, financial institutions bear a significant responsibility in leading the efforts to curb greenhouse gas emissions. Also, greenhouse gas emissions are the result of market failures; therefore, there is a need for governments to act. The paper also examines the challenges facing green banking and its prospects. The conclusion is that while green banking displays good growth prospects, there exists three major challenges: (1) limited awareness of green products and services that banks can offer, (2) greenwashing, and (3) the high cost of offering green financial services. Despite these challenges, the paper affirms the potential of green banking to promote sustainability and mitigation of the environmental crisis.
Keywords: banking; climate change; dept.eco; environmental crisis; environmental degradation; financial institutions; green banking; greenwashing; peer-reviewed; sustainability; sustainable financing

Unanticipated money growth and unemployment in the Philippines - Patalinghug, Jason C. (Journal of Applied Economic Sciences (JAES), 2024)
The Philippines has had high levels of unemployment for years. During the 2000s, the unemployment rate hovered between seven and ten percent. High unemployment can have adverse effects on individuals and society. The question that this paper analyses is how unanticipated money growth affect the unemployment situation in the Philippines. There has been literature on the relationship between unanticipated growth on the money supply and unemployment. The paper proposes that only unanticipated money movements will affect real economic variables like unemployment and the output level. In order to test our hypothesis, it is important that we need to quantify the concepts of anticipated and unanticipated money movements. This paper uses time-series data on several economic variables as well as a model based on Geetha et al. (2023). Using an error-correction model, the results show that an unanticipated increase in M2 money is a factor that contributes to unemployment in Philippines.
Keywords: Philippines; dept.eco; peer-reviewed; time-series data; unanticipated money; unemployment

What increases the urban–rural gap in firm entry rates? - Kim, Younjun; Orazem, Peter (Small Business Economics, 2025)
Keywords: Agglomeration; Business; Economic geography; Economics; Entrepreneurship; Finance; Firm entry; Human capital; J24; M13; R11; Rural; Urban; dept.eco; peer-reviewed

Corruption, Natural Capital and Economic Development: A Dynamic GMM Analysis - Ang, Joshua; Patalinghug, Jason (Review of Economic Analysis, 2025)
Using a dynamic panel dataset of 150 countries for the period of 2006-2018 and a two-step system GMM estimation model, this paper shows that natural resources have a positive effect on economic development while holding corruption constant. Our findings support the notion that natural resources have a positive effect on the economy of a nation. When a country has less corruption, it improves the appropriation of economic gains from natural resources which serves as natural capital that would drive further capital accumulation and further development. We also find that physical capital, human capital, and freedom from corruption show strong positive effects on economic development, controlling for other economic and institutional variables.
Keywords: Corruption; Dynamic Panel Study; Econometrics; Economic Development; Economics; Human Capital; Language change; Natural Resources; Physical Capital; dept.eco

Parental Education Matters for Adolescent Health: The Importance of Parental Education in the US - Yu, Jia (Journal of Studies in Social Sciences, 2015)
Parental Education Matters for Adolescent Health: The Importance of Parental Education in the US
Keywords: dept.eco

Avoidable Mortality and Healthcare Expenditure in OECD Countries: DEA and SFA methods to health expenditure efficiency - Yu, J. (J Adv Soc Sci Hum, 2016)
Keywords: dept.eco

The Determinants of Human Trafficking: A US Case Study - Jac‐Kucharski, Alicja (International Migration, 2012)
Human trafficking is a global problem. In this paper, I seek to find the determinants of international human trafficking by using the US as a case study. Previous studies have drawn primarily from the migration literature, proposing hypotheses that focus on economic factors, the level of democracy and other “push” factors in the countries of origin that create incentives for individuals to migrate. However, we know that international human trafficking is an involuntary form of migration and may be influenced by additional factors. I hypothesize that factors that influence the cost–benefit calculation of the trafficker determine the volume of human trafficking, in addition to the factors that affect the size of the pool of trafficking victims. I test my theory using the negative binomial regression model. My results indicate that while income inequality within a country and poor protection of women's rights are likely to produce a specific pool of victims, it is the reduction of operational costs for the trafficker that increases the number of individuals who are trafficked.
Keywords: dept.eco

The Effect of Advertising and In-Store Promotions on the Demand for Chocolate - Patalinghug, Jason (International Journal of Economics and Finance, 2015)
This paper analyzes the effect of TV advertising and in-store displays on the sales of chocolates. I examine which method is more effective in gaining customers and in increasing total sales. Also, I look at the evidence to see whether the lack of advertising by a firm will hurt the industry as a whole. In this paper, I use a nested logit model on scanner data obtained by the Zwick Center for Food and Resource Policy at the University of Connecticut to examine the effect of TV advertising on chocolate sales. The results show that in-store displays and advertising both help increase the demand for chocolate.
Keywords: dept.eco

A Case Study of Organizational Form: Hershey versus Mars - Patalinghug, Jason C. (e-Journal of Social & Behavioural Research in Business, 2016)
Purpose: This study examined the history, growth and structure of two of the world's largest confectionery makers, Hershey and Mars, to determine why these two companies chose their current organizational form. Design/method/approach: This paper starts off with an analysis of the industrial foundation which is a common organizational form in Europe but rarely found in the United States. A historical analysis is then made of both Hershey and Mars using literature from economics, law, history and management to come up with answers as to why the two corporations are organized the way they are today. Findings: The study found that Hershey adopted the industrial-foundation organizational form based on the donor-agency theory which assures donors that their donations are not redistributed as profits to residual claimants. The non-distribution constraint in the Hershey Trust Company prevents dividends (donations) from being redistributed to residual claimants, and that the non-distribution constraint makes more sense for Hershey because its founder, Milton Hershey, expressed his preference to leave a long lasting legacy. The study also found that Mars has chosen a family-controlled organizational form based on the competitive advantage theory which postulates that firm value is maximized when families retain control, benefitting both family and nonfamily shareholders. Originality/value: There have been few studies on the history and organizational evolution of the American confectionery industry. The study is unique as it addresses some gaps in the literature as it provides a historical and institutional study into that particular industry.
Keywords: Business planning; Hershey Trust Co.; Martian aeronautics; Organization; Profitability; corporate governance; dept.eco; economics of organization; family owned firms; industrial foundation

Eighty years of research on rural economic development, agglomeration, migration, commuting, income, innovation, and entrepreneurship: The Iowa State human capital tradition - Artz, G.M.; Cho, I.; Guo, Z.; Kim, Y.; Orazem, Peter; Yu, Li (2015)
Wallace Huffman continued the tradition of research on Midwest rural labor markets at Iowa State University that was begun in the 1930s by his advisers T.W. Schultz and D. Gale Johnson. We review the lessons learned from this research about the wisdom of policies aimed at retaining population in rural areas in the face of market forces and technological changes that create incentives to migrate to urban areas. Professor Huffman's teaching and lessons learned from the Iowa State Human Resources Workshop continues to shape recent research on the roles of agglomeration economies, information technologies, and returns to human capital on the strength of rural labor markets and policies regarding rural economic development.
Keywords: dept.eco

Understanding Behavioral Explanations of the WTP-WTA Divergence Through a Neoclassical Lens: Implications for Environmental Policy - Kim, Younjun; Kling, Catherine; Zhao, Jinhua (Annual Review of Resource Economics, 2015)
The often observed empirical divergence between WTA and WTP measures of welfare change continues to be a topic of interest to both theoretical and applied economists. The divergence has particularly important implications for environmental policy. In this article, we review behavioral and other explanations of the disparity, with a focus on their connections to neoclassical welfare theory, and evaluate the empirical evidence of these explanations through the same lens. Some explanations of the disparity are consistent with neoclassical models, and some are not. Likewise, some imply that the divergences are attributed to underlying preferences (neoclassical or not), whereas others suggest that the divergences are due to elicitation methods, cognitive limitations, or other non-preference-related reasons. We argue that the source of the divergence can inform the choice of which measure, WTP or WTA, to use in a given empirical application.
Keywords: dept.eco

Does Agglomeration Matter Everywhere?: New Firm Location Decisions in Rural and Urban Markets - Artz, Georgeanne M.; Kim, Younjun; Orazem, Peter F. (Journal of Regional Science, 2016)
We test whether commonly used measures of agglomeration economies encourage new firm entry in both urban and rural markets. Using new firm location decisions in Iowa and North Carolina, we find that measured agglomeration economies increase the probability of new firm entry in both urban and rural areas. Firms are more likely to locate in markets with an existing cluster of firms in the same industry, with greater concentrations of upstream suppliers or downstream customers, and with a larger proportion of college-educated workers in the local labor supply. Firms are less likely to enter markets with no incumbent firms in the sector or where production is concentrated in relatively few sectors. The same factors encourage both stand-alone start-ups and establishments built by multiplant firms. Commuting decisions exhibit the same pattern as new firm entry with workers commuting from low to high agglomeration markets. Because agglomeration economies are important for rural firm entry also, policies encouraging new firm entry should focus on relatively few job centers rather than encouraging new firm entry in every small town.
Keywords: dept.eco

U.S. Macroeconomic News and International Stock Prices: Evidence from Newspaper Coverage - Birz, Gene; Dutta, Sandip (Accounting and Finance Research, 2016)
Existing studies provide mixed evidence that the U.S. macroeconomic news impacts international stock prices. We believe this may be related to the fact that economic surprises may not capture how investors interpret macroeconomic releases in various economic conditions. Consequently, we follow Birz and Lott (2011) and use newspaper coverage of economic releases as a measure of news. We argue that in addition to capturing the surprise component of macroeconomic releases, newspaper coverage provide interpretation of these releases similarly to how investors may interpret them in various economic conditions. Out of 15 examined international stock markets, we find that the U.S. macroeconomic news impacts stock returns of 12 countries.
Keywords: dept.eco

Information technology adoption and the growth of nonemployer businesses - Kim, Y.; Thompson, E. (Journal of Economics and Management Strategy, 2024)
The growth of nonemployer businesses as a share of the working-age population has been little studied relative to the decline of employer business rate in the United States. We show that local labor markets specializing in routine task-intensive jobs have experienced a higher adoption of information technology as well as the growth of nonemployer businesses primarily through increasing self-employment in nonroutine manual task-intensive jobs that are less frequently outsourced to business service firms. © 2024 Wiley Periodicals LLC.
Keywords: dept.eco; peer-reviewed

How human capital prevents intergenerational poverty transmission in rural China: Evidence based on the Chinese general social survey - Chen, Hong; Yu, Jia; Zhang, Ze; Li, Yuheng; Qin, Lijian; Qin, Mingshuai (Journal of Rural Studies, 2024)
Keywords: dept.eco; peer-reviewed

Challenges and Futures of Long-Term Care Industry after COVID-19 Pandemic - Yu, Jia (Psychosocial, Educational, and Economic Impacts of COVID-19, 2022)
COVID-19 pandemic has affected people’s daily life dramatically since December 2019. More than 211 million cases and 4.42 million deaths have been reported and confirmed all over the world. Long-term care facilities are taking the biggest hit during this pandemic, even after the spread-out of the vaccines. Globally, residents in long-term care facilities have experienced disproportionately high morbidity and mortality from COVID-19. Elderlies residing in long-term care facilities have the greatest susceptibility to COVID-19 and the poorest outcomes from infections. This chapter overviewed the insight, impact, and challenges of COVID-19 on the residential care homes in UK, US, and Australia and provided possible implications for the long-term care market post-pandemic.
Keywords: dept.eco

The Effect of Property Rights on GDP per Capita - Ang, Joshua Ping; Patalinghug, Jason C. (The Empirical Economics Letters, 2020)
Keywords: dept.eco; peer-reviewed

COVID-19: effectiveness of socioeconomic factors in containing the spread and mortality - Book Chapter - Patalinghug, Joshua Ping Ang, Fang Dong, Jason (The Political Economy of Covid-19, 2022)
This paper presents a study on 80 countries that evaluates the socioeconomic factors in containing the spread and mortality of COVID-19. Our results show that the long-term social factors such as lower personal freedom, better education in science, and past coronavirus outbreak experience are more effective than the economic factors such as higher healthcare-associated factors per 1000 population and larger GDP. However, using GDP per capita as the instrumental variable, we also find that the richer countries with a high degree of personal freedom have a higher number of infection or death cases per million population because they would be less likely to adhere to and implement the policy of the movement restrictions to restrict their access to goods and services.
Keywords: dept.eco

Contemporary protectionism-causes and consequences - Grubacic, Sanja; Schuster, Julian (The Business & Management Review, 2019)
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Performance of State-Owned Enterprises: A Comparative Analysis of Ethiopian Airlines and Ghana Airways - Andoh, Samuel K.; Gebremariam, Yilma; Thorson, James; Bodo, Peter (American Journal of Management, 2019)
This paper examines the performance of two state-owned airlines: Ethiopian Airlines and Ghana Airways. While Ethiopian Airlines continues to operate successfully, the other airline has gone out of business. In an industry characterized by heavy competition and a high rate of failure, the success of the state- owned Ethiopian Airlines is intriguing. The evidence shows that Ethiopian Airlines outperforms the industry on some important benchmarks. These findings suggest that being a state enterprise is not necessarily a characteristic that leads to failure. Corporate culture and governance appear to be important factors in the success of Ethiopian Airlines.
Keywords: Airlines; Business And Economics--Management; Business metrics; Economic growth; Economic theory; Emerging markets; Failure; Profits; Public enterprise; Stockholders; Success; dept.eco; peer-reviewed; ⛔ No DOI found

Bilateral environmental aid and trade - Yoon, Sang W.; Kim, Younjun; Park, Byoung G.; Yoon, Chang-Ho (Applied Economics, 2024)
The paper estimates the determinants of the growing volume of bilateral environmental aid for the mitigation of climate change using an empirically testable multilateral framework in which both donors and recipient countries compete in world export markets. As the potential donors weigh environmental benefits against the economic costs of providing aid, strategic interactions between the donors and the recipient countries as well as among the donors, influence the evolution of environmental aid. The paper shows that while the volume of bilateral environmental aid increases with the recipient country’s credible environmental commitment and bilateral trade volume, the competitive pressure in the export market reduces bilateral environmental aid. Free-riding incentives prevail among the individual donors, whereas the multilateral environmental aids that aim to restore the loss of global environmental resources without altering individual trade competitiveness can increase bilateral environmental aids.
Keywords: Environmental ODA; F18; F35; Q54; competitive threats; credible commitment; dept.eco; international trade; multilateral institutions; peer-reviewed

Sustainable growth with pollution augmenting technological changes - Yoon, Sang Won; Yoon, Chang-Ho (2023)
Disruptive technological changes, including carbon capture and storage, can have macroeconomic rebound effects that pose a threat to long term environmental sustainability when not accompanied by pollution taxes. The paper demonstrates that when the elasticity of intertemporal substitution is less than one, implementing a Pigouvian tax effectively stabilizes pollution emissions, regardless of technical and consumption elasticities of substitution. However, if the elasticity of intertemporal substitution exceeds one, flexibility in technical or consumption substitution could cause sustainable growth to falter. The policy implications concerning the role of subsidies for clean technology are discussed.
Keywords: Elasticity of intertemporal substitution; Optimal pollution tax; Sustainable development; dept.eco; energy rebound; technological change

International comparison on economics impact from the COVID-19 pandemic: policy analysis - Supple, Brandon; Yu, Jia (Medical Research Archives, 2023)
Keywords: SCSU-student; dept.eco; peer-reviewed

The Philippines in a Liberalizing Trade Environment: Issues and Prospects - Patalinghug, Jason (Economic Insights - Trends & Challenges, 2020)
Free trade agreements (FTAs) have mushroomed in the Asia-Pacific region over the past fifteen years. The Philippines is trying to forge several of these agreements in order to stay competitive. This paper examines the emergence of the Association of South East Asian Nations (ASEAN) as well as the ASEAN Free Trade Agreement. This paper will discuss the advantages for the country by joining both the AFTA and the Japan Philippines Economic Partnership Agreement. It will also discuss several free trade agreements that are in effect in the region as well as efforts by the country to join the Trans-Pacific Partnership (TPP) and the Regional Comprehensive Economic Partnership (RCEP). For the country to be a member of the TPP certain institutional reforms are needed to be put in place. The studies examined in this paper show that these FTAs in general have a positive effect on the Philippine economy.
Keywords: PHILIPPINES; REGIONAL Comprehensive Economic PartnershipCOMMERCIAL treatiesTRANS-Pacific PartnershipFREE tradePARTNERSHIP agreements; dept.eco; peer-reviewed; ⛔ No DOI found

Effects of System Noise and Bribery on Collective Decision Rules. - Bodo, Peter (2008)
Developed and used Monte Carlo simulation models to test the effects of system moise and bribery on collective decision rules. He wrote simulation software, ran the simulations after debugging the software, analyzed the results and wrote a research paper, and presented the paper at the annual conference of the Eastern Economic Association. The paper will be published next year.
Keywords: dept.eco; faculty_collection; sabbatical_report

Occupational Mortality, Age at Marriage and Marital Fertility in Early Twentieth Century England and Wales. - Mills, Judith Woerner (2003)
Keywords: dept.eco; faculty_collection; sabbatical_report

[Translation of 2 Books on the Financing of the French Crown in the 13th Century] - Eldridge, Robert (2001)
Keywords: dept.eco; faculty_collection; sabbatical_report

Currency Substitution in Developing Countries. - Andoh, Samuel (Spring; Economics/Finance., 2000)
Keywords: dept.eco; faculty_collection; sabbatical_report

Exchange Rate Management in Advanced Transition Economics - Grubacic, Sanja (2017)
The purpose of my sabbatical leave was to enable me to engage in writing a manuscript on Exchange Rate management in Advanced Transition Economics. This project involved gathering, analyzing, and preparing for publishing the new empirical evidence on behavior of exchange rates in several economies of East and Central Europe. The analysis intended to contribute to a theoretical and empirical literature on the importance of foreign exchange markets and exchange rate management in promoting a country's internal and external balance.
Keywords: dept.eco; faculty_collection; sabbatical_report

Essentials of Money, Banking and Financial Institutions: With Applications to the Developing World - Andoh, Samuel K. (Lexington Books, 2014)
Essentials of Money, Banking and Financial Institutions builds on the essential concepts of money and banking and applies them in the context of developing countries. Frequent comparisons between developed and developing countries are made to enable students to make proper inferences about the efficacy of certain concepts.
Keywords: Developing countries; Developing countries; Banks and banking; Developing countries; Economic development; Finance; Money market; dept.eco; faculty_collection

The Development of Capital Markets and Economic Growth in Transition Economies: Sabbatical Fall 2009 - Grubacic, Sanja (2009)
This project involved gathering, analyzing, and preparing for publication the new empirical evidence on the working of capital markets in several economies of East and Central Europe, additionally providing material to enrich the curriculum in economics and finance. It also provided material for a conference presentation.
Keywords: dept.eco; faculty_collection

Unlocking Opportunities for Migrant Workers in China: Analyzing the Impact of Health Insurance on Hukou Switching Intentions - Chen, Hong; Yu, Jia; Qin, Mingshuai; Wang, Yangyang; Qin, Lijian (Sustainability, 2023)
The Chinese urban–rural binary health insurance structure has contributed to a significant urban–rural segmentation and regional fragmentation, which will affect labor mobilization and urbanization. The purpose of this research is to study whether and how urban–rural binary health insurance impacts the intentions of migrant workers to switch between rural and urban hukou. Pooled data were drawn from China Migrants Dynamic Survey, collected by the National Health Commission of China. The study applied the instrument variable model due to the existence of the endogeneity; and the IVprobit model to conduct the empirical analysis. Our findings are as follows: (1) the urban–rural binary health insurance affects migrant workers’ intentions to switch to urban hukou significantly. (2) The negative impact of originally rural health insurance on migrant workers’ intention of switching to urban hukou is relatively large for low-education-level migrant workers. (3) Compared with new generation of migrant workers, old migrant workers have higher health insurance dependency levels. Finally, our research suggested several policy implications, such as accelerating the establishment of a unified urban–rural health insurance system, increasing the urban health insurance participation rate of migrant workers in their working cities, and including migrant workers in the scope of equal access to urban public services, etc. All the policy suggestions are essential in order to accelerate the citizenization of migrant workers, improve the quality of urbanization, and promote the construction of a unified national labor market.
Keywords: dept.eco; intention of switching to urban hukou; migrant workers; peer-reviewed; urban–rural binary health insurance

Overconfidence and Public Intoxication Arrest: Evidence from a University Town Police Log - Hoffman, Elizabeth; Kim, Younjun (The B.E. Journal of Economic Analysis & Policy, 2022)
We show that overconfident individuals are likely to be arrested for public intoxication by using arrest records from a university town police log. This relationship is robust to various control variables such as risk aversion, time discounting, present bias, self-control, selfishness, loss aversion, and socializing with peers arrested for public intoxication. However, this relationship is no longer significant using only self-reported arrest data. We hypothesize that overconfident individuals are likely to underreport their arrests. This result has important implications for the use of self-reported data on public intoxication arrests rather than actual arrest records.
Keywords: arrest; dept.eco; overconfidence; public intoxication

'How could I choose my health insurance plan?' Determinants of employer-sponsored health insurance plan selection: application of machine learning technique - Zhang, Yi; Yu, Jia (International Journal of Economics and Business Research, 2022)
Selecting the appropriate, reasonable, and affordable health insurance plan becomes a very important question to solve for both employers and employees. Our research tries to locate the factors determining private sector health insurance plan enrolment decision, and also provides a guideline to both private companies and employees on health insurance plan selection strategies. By using Kaiser Family Foundation Annual Employer Health Benefits Survey (KFF EHBS) data, we apply random decision forest machine learning methodology to study the determinants of employees' health insurance selection, as well as to compare the prediction accuracy among different methodologies. The results indicate: 1) the employees at large firms and the firms with higher eligible rate would tend to choose PPO plan; 2) employees who need family coverage would have different choices comparing employees who seek for single coverage only; 3) employer's contribution and annual total contribution to the health insurance plan are the most important determinants on employees' insurance selection. The conclusion also can provide some suggestions to insurance companies on health insurance package design for different types of employers and employees.
Keywords: HDP; PPO; dept.eco; health insurance; high-deductible health plan; logit regression; machine learning; peer-reviewed; random decision forest

A lidar collaboratory data management system - Sharma, N.C.P.; Parikh, J.A.; Clark, M. (2006)
A data management system has been developed for the Connecticut State University (CSU) Lidar Collaboratory to facilitate user authentication, scheduling of remote lidar instrumentation control sessions, storage and retrieval of lidar datasets and generation of new data products. In addition to providing for efficient archival and retrieval of lidar data products, a major design goal of the data management system is to support collaborative, multidisciplinary, atmospheric sciences research projects. In this paper, we describe the framework of the CSU Lidar Collaboratory data management system and how the system interacts with the data acquisition and data analysis software.
Keywords: Atmospheric optics; Computer programming; Computer supported cooperative work; Connecticut State University (CSU); Data management systems; Data reduction; Image retrieval; Information management; Optical radar; Remote lidar instrumentation; User authentication; dept.csc

Routine-biased technological change and declining employment rate of immigrants - Kim, Younjun; Thompson, Eric (Eastern Economic Journal, 2021)
We find that routine-biased technological change decreases the employment-to-population ratio of foreign-born population over the last three decades (1980–2010). This impact is greater for foreign-born population with lower English proficiency. As computerization and automation substitute for workers in routine occupations, switching from routine jobs to non-routine cognitive jobs may be more challenging for foreign-born workers than for native workers. © 2021, EEA.
Keywords: dept.eco

Property rights and economic growth: A dynamic GMM analysis - Ang, J.; Patalinghug, Jason (Economics Bulletin, 2021)
This paper examines the role of property rights and other factors to the growth of real gross domestic product (GDP) per capita. We show using a two-step system generalized method of moments (GMM) dynamic model and a panel data set of around 150 countries from 2006 to 2018 that property rights have a positive and significant effect on the growth of real GDP per capita. The paper also found that human capital, physical capital and inflation have significant effects on real GDP per capita growth. © 2021. All Rights Reserved.
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Property, Institutions, and Social Stratification in Africa - Andoh, Samuel K. (African and Asian Studies, 2020)
Keywords: book.review; dept.eco

Which Small Towns Attract Start-Ups and Why? Twenty Years of Evidence from Iowa - Artz, Georgeanne M.; Kim, Younjun; Orazem, Peter F.; Han, Peter J. (American Journal of Agricultural Economics, 2021)
Using data on a sample of small Iowa towns consistently collected over two decades, we investigate how agglomeration economies, social capital, human capital, local fiscal policy, and natural amenities affect new firm entry. We find that human capital and agglomeration are more conducive to new firm entry than are natural amenities, local fiscal policy, or social capital. The impact of local fiscal policy is too small to overcome the locational disadvantages from insufficient endowment of human capital and agglomeration. A rural development approach that encourages firm entry in rural towns with the largest endowments of human capital and market agglomeration would be more successful than trying to raise firm entry in every town.
Keywords: M13; R11; R39; agglomeration; dept.eco; firm location; human capital; peer-reviewed; rural

Economic development in Ghana and Malaysia: A comparative analysis - Andoh, S.K.; de Gannes Scott, B.J.; Ofori-Abebrese, G. (Economic Development in Ghana and Malaysia: A Comparative Analysis, 2020)
Economic Development in Ghana and Malaysia investigates why two countries that appeared to be at more or less the same stage of economic development at one point in time have diverged so substantially. At the time of their independence from the UK in 1957, both Ghana and Malaysia were at roughly the same stage of economic development; in fact, Ghana's real per capita income was slightly ahead of Malaysia's. Since then, Ghana's development has been sluggish, while Malaysia's economy has taken off into sustained growth and today, the real per capita income of Malaysia is about five times that of Ghana. This volume examines the pre-colonial and colonial economies of both countries, and the economic policies pursued after independence. In doing so, it aims to identify policies which might have contributed to Malaysia's development and those which might have slowed Ghana's. The authors ask whether lessons can be learned from the successes of countries such as Malaysia. This detailed comparative analysis will be useful to students and researchers of development economics as well as public policy makers in developing countries. It is written in language which makes it accessible to the general reader. © 2020 Samuel K. Andoh, Bernice J. deGannes Scott and Grace Ofori-Abebrese. All rights reserved.
Keywords: dept.eco; peer-reviewed

COVID-19: effectiveness of socioeconomic factors in containing the spread and mortality - Ang, Joshua Ping; Dong, Fang; Patalinghug, Jason (International Review of Applied Economics, 2021)
This paper presents a study on 80 countries that evaluates the socioeconomic factors in containing the spread and mortality of COVID-19. Our results show that the long-term social factors such as lower personal freedom, better education in science, and past coronavirus outbreak experience are more effective than the economic factors such as higher healthcare-associated factors per 1000 population and larger GDP. However, using GDP per capita as the instrumental variable, we also find that the richer countries with a high degree of personal freedom have a higher number of infection or death cases per million population because they would be less likely to adhere to and implement the policy of the movement restrictions to restrict their access to goods and services. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: COVID-19; Coronavirus; Gross Domestic Product; dept.eco; disease control; disease spread; epidemic; global perspective; mortality; pandemic; peer-reviewed; regression analysis; socioeconomic conditions

Derivative use, ownership structure and lending activities of US banks - Abugri, Benjamin A; Osah, Theophilus Teye (Journal of Economics and Finance, 2021)
Following the 2007–2008 financial crisis, there is widespread interest in understanding how derivative use drives bank lending behavior. Our paper examines the impact of bank ownership structure on the relationship between derivative use and lending activities of U.S. banks. We find that lending recovered faster in larger banks than smaller banks post-crisis and in line with Diamond’s (Diamond DW 1984 Financial intermediation and delegated monitoring. Rev Econ Stud 51:393–414) systemic risk reduction theory, derivative use is positively associated with lending growth. Ownership is significant in explaining the magnitude of the relationship even after controlling for alternative specifications of the derivative use variable. In both normal and crisis periods, the speed of adjustment of lending to derivatives use by stock banks lags that of mutual banks. We suggest that speculative trading in derivatives substitutes for lending growth to a larger extent for stock banks compared to mutual banks. These findings may have important implications for investors and bank regulators. © 2020, Academy of Economics and Finance.
Keywords: dept.eco; dept.fin; peer-reviewed

No more nursing homes? Changes in consumer preferences for long-term care facilities following COVID-19 - Schultz, Amber F; Yu, Jia (British Journal of Healthcare Management, 2020)
Since the first COVID-19 case was discovered in December 2019, over 12.1 million cases have been reported in more than 188 countries and territories. In the USA, the Centers for Disease Control and Prevention has confirmed almost 3.05 million COVID-19 cases, with more than 132 000 deaths. The COVID-19 pandemic has had a particularly dramatic impact on the elderly and those with chronic underlying medical disorders. Before the second outbreak in July, long-term care facilities were the most severely affected in terms of case numbers, especially nursing homes. This article provides information and insight into the potential changes in consumer preferences toward long-term care facility selection and the possible structural change of the long-term care industry in three aspects; structure, conduct and performance. © 2020 MA Healthcare Ltd. All rights reserved.
Keywords: Covid-19; Home care service; Long-term care facility; Nursing home; dept.eco; peer-reviewed

Professional sovereignty revisited: The Network Transformation of American Medicine?. - Savage, Deborah A (Journal of health politics, policy and law, 2004)
Keywords: *Hierarchy, Social; *Professional Autonomy; *Social Change/hi [History]; *Sociology, Medical/hi [History]; Education, Medical; Education, Medical/hi [History]; Health Policy; Health Policy/hi [History]; Hierarchy, Social; History, 19th Century; History, 20th Century; Humans; Politics; Power (Psychology); Power, Psychological; Professional Autonomy; Professional Corporations; Professional Corporations/hi [History]; Social Change; Sociology, Medical; Sociology, Medical/ec [Economics]; United States; dept.eco; health care organization; health care planning; health care system; health economics; history of medicine; hospital; medical decision making; medical education; medical practice; medical profession; medical society; medical technology; politics; review; social evolution; social interaction; social structure

Hedge fund crisis and financial contagion: evidence from long-term capital management - Halstead, John M; Hegde, Shantaram P; Klein, Linda S (The Journal of Alternative Investments, 2005)
Keywords: dept.eco; dept.fin

Monetary policy, composite leading economic indicators and predicting the 2001 recession - Mostaghimi, M (Journal of Forecasting, 2004)
On 26 November 2001, the National Bureau of Economic Research announced that the US economy had officially entered into a recession in March 2001. This decision was a surprise and did not end all the conflicting opinions expressed by economists. This matter was finally settled in July 2002 after a revision to the 2001 real gross domestic product showed negative growth rates for its first three quarters. A series of political and economic events in the years 2000-01 have increased the amount of uncertainty in the state of the economy, which in turn has resulted in the production of less reliable economic indicators and forecasts. This paper evaluates the performance of two very reliable methodologies for predicting a downturn in the US economy using composite leading economic indicators (CLI) for the years 2000-01. It explores the impact of the monetary policy on CLI and on the overall economy and shows how the gradualness and uncertainty of this impact on the overall economy have affected the forecasts of these methodologies. It suggests that the overexposure of the CLI to the monetary policy tools and a strong, but less effective, expansionary money policy have been the major factors in deteriorating the predictions of these methodologies. To improve these forecasts, it has explored the inclusion of the CLI diffusion index as a prior in the Bayesian methodology. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: Bayesian probability forecasting; Classical statistical decision theory; Composite leading indicators; Composite leading indicators (CLI); Composite leading indicators diffusion index; Diffusion index; Geochronology; Industrial economics; Information theory; Monetary policy; Predicting recessions; Probability; Public policy; Quality control; Set theory; Statistical methods; US economy; Us economy; dept.eco; dept.fin

Orange county bankruptcy: financial contagion in the municipal bond and bank equity markets - Halstead, John M; Hegde, Shantaram P; Klein, Linda S (The Financial Review, 2004)
We examine the spillover wealth effects of the Orange County, California bankruptcy announcement in December 1994 on municipal bonds, municipal bond funds, and bank stocks. This bankruptcy is prominent because of unprecedented losses and because it was caused by a highly leveraged derivatives strategy rather than a shortage of tax revenues and excess spending. We find contagion in the bond market with significantly negative abnormal returns for municipal bond funds without direct exposure to Orange County and for non-Orange County municipal bonds. In addition, our findings suggest the contagion spills over to the common stocks of investment and commercial banks that deal in or use derivatives; however, the equities of banks unexposed to derivatives are not affected. © 2004 Blackwell Publishing Ltd.
Keywords: Bank equity; Contagion; Derivatives; Fixed income; G2/H3/K2; Municipal financing; dept.eco; dept.fin

Currency substitution: evidence from latin america - Prock, Jerry; Soydemir, Gokce; Abugri, Benjamin A (Journal of Policy Modeling, 2003)
Currency substitution represents a shift from domestic currency to foreign currency and is often related to times of high and variable inflation. In this paper, we investigate the extent of currency substitution in Argentina, Brazil and Mexico using a vector error correction (VEC) model. We empirically test this hypothesis by introducing artificial shocks to the system of equations and find that M1 response to a one standard deviation increase in that country's interest rate is negative and significant for Argentina and Brazil but not for Mexico. An artificially introduced one standard deviation increase in nominal exchange rate results in a statistically significant increase in M1 in Argentina and Brazil but again not for Mexico. Based on the patterns of the impulse response functions (IRFs) and the magnitude of the coefficients, we conclude that currency substitution occurs to a greater extent in Argentina and Brazil than Mexico. This is reflective of the implementation of relatively more credible macroeconomic policies in Mexico after the December 1994 crisis. Thus from a policymaking perspective, it is important to consider that the greater the degree of currency substitution, the more sensitive a country's monetary aggregates are to sudden movements in exchange rates, productivity and interest rates. (C) 2003 Society for Policy Modeling. Published by Elsevier Science Inc. All rights reserved.
Keywords: Currency; Latin America; Substitution; VEC; dept.eco; dept.fin

Book Review: Birthquake: the baby boom and its aftershocks. by diane j. macunovich. chicago: the university of chicago press, 2002. pp xiii, 314. 37.50 - Mills, Judith Woerner (The Journal of Economic History, 2003)
Keywords: book.review; dept.eco; dept.fin

Stability of the money demand function: evidence from Ghana - Andoh, SK; Chappell, D (Applied Economics Letters, 2002)
This paper estimates the demand for money (M2) in Ghana for the period 1960 to 1996. The hypothesis is that the different macroeconomic adjustment policies (privatization, removal of foreign exchange controls etc.) which began in the mid 1980s would alter the demand for money function. The results of the study clearly show a structural break in the demand for money function in 1983.
Keywords: dept.eco; dept.fin; peer-reviewed

In-class simulations of the iterated prisoner's dilemma game - Bodo, Peter (Journal of Economic Education, 2002)
The author developed a simple computer program for the in-class simulation of the repeated prisoner's dilemma game with student-designed strategies. He describes the basic features of the software and presents two examples for the use of the program in teaching the problems of cooperation among profit-maximizing agents.
Keywords: Computer simulation; Experiments; Prisoner's dilemma; Repeated games; dept.eco; dept.fin

Market efficiency and non-linear dependence in the Czech crown/US dollar foreign exchange market - Chappell, David; Eldridge, Robert M (Discussiones Mathematicae Probability and Statistics, 2002)
Keywords: dept.eco; dept.fin

Exchange rate adjustment in partially liberalized economy - Grubacic, Sanja (Economics of Planning, 2002)
This paper develops a model of exchange rate determination in partially liberalized post-socialist economy that operates under soft budget constraints in nontradable sectors. The model captures the factors that determine the evolution of a country's external balance during the initial phase of economic liberalization. Three types of disturbances are the center of analysis: liberalization of trade and foreign exchange regime, devaluation, and price liberalization. We show that the real exchange rate appreciation may either improve or worsen the trade balance depending on the sources of this appreciation. Thus, we argue that the real exchange rate cannot reflect true country's competitiveness unless all sectors are equally exposed to hard budget constraints. The model implications are further analyzed through the empirical evidence on the relationship between the real exchange rate and trade balance in three selected East European countries.
Keywords: Europe; Exchange rate; External balance; Liberalization; Post-socialist economy; Soft budget constraint; balance of trade; competitiveness; dept.eco; dept.fin; exchange rate; external balance; liberalization; post-socialist economy; real exchange rate; soft budget constraint

Soft-landing monetary policy, composite leading economic indicators, and predicting the 2001 recession - Mostaghimi, Mehdi (Social Science Research Network, 2002)
Keywords: dept.eco; dept.fin

Corporate groups, capital investments and stock returns in japan - Wei, Kuochiang; Xie, Feixue; Titman, Sheridan (APFA/PACAP/FMA International Finance Conference in Tokyo, Japan, 2002)
Keywords: dept.eco; dept.fin

Information collection strategic design in experts-assisted decision making paradigm - Mostaghimi, Mehdi (Group Decision and Negotiation, 2001)
In an experts-assisted decision making paradigm, the information collection design becomes a strategic variable under a weak assumption that the final decision is dependent on the design used to collect information as well. As a result, the same information of the experts and the decision maker about the problem can potentially produce different final decisions for different information collection designs. The implication is that a decision maker can strategically select a design which serves his/her objective. This paper uses a Bayesian estimation methodology for combining experts' information with the decision maker's prior. An information collection process is designed by setting constraints on this model. Several designs are developed here using such controlled factors as a one-stage versus a two-stage decision process, experts' rank ordering, and group versus individual lobbying/consultation. An example is provided to illustrate the applicability of the concept. It is shown that the information produced in the process of producing a decision can also give insights into the impacts of the decision maker and the experts on the decision.
Keywords: Bayesian method; Experts-assisted decision making; Information theory; Reaching a consensus; dept.eco; dept.fin; experts-assisted decision making; information theory; reaching a consensus

Econometric analysis of foreign reserves and some macroeconomic variables in Nigeria (1970–2007) - Olokoyo, Felicia O; Osabuohien, Evans; Salami, O Adeleke (African Development Review, 2009)
P¿Countries are showing interest in accumulating foreign reserves to ensure macroeconomic stability. There has been some debate whether to beef up the level of nations' foreign reserves or make it lower, especially in developing countries like Nigeria. Whereas some argue that the foreign reserve determines the country's rating in the global market, others hold opposing views. In this light, this paper examined the interactive influence of foreign reserve (FRS) on some macroeconomic variables such as: economic size (GDP); trade; level of capital inflows (KFL); exchange rate (EXR); and inflation. Analyzing secondary data from CBN statistical bulletins (1970-2007), the econometric results obtained from cointegration test, vector error correction (VEC) within the framework of autoregressive distributed lags (ARDL) revealed the following: (1) existence of a long-run relationship between the variables and two cointegrating equations; (2) possibility of convergence of the variables from the short run to the long run with slow speed of adjustment. It is thus the conclusion of this paper that accumulation of large foreign reserves is not very productive in Nigeria due to its inability to induce some of the macroeconomic variables.
Keywords: dept.eco; dept.fin

Testing Trade-Off and Pecking Order Models Under Different Institutional Environments - Farhat, Joseph B.; Cotei, Carmen; Abugri, Benjamin A. (SSRN Electronic Journal, 2009)
In this paper, we examine the differences in information asymmetry and financing patterns and a generalized version of the trade-off theory across countries with different institutional environments. We find that firms in Civil law countries have higher information asymmetry, rely more on internally generated funds, and use more short-term debt to finance their financing deficit, relative to those in Common law countries. In both Civil law and Common law countries, factors suggested by the trade-off theory explain the financing deficit coefficient in the generalized version of the trade-off model. Overall, the generalized version of the trade-off theory provides a better explanation for the changes in capital structure relative to the pecking order theory, even in countries with higher information asymmetry.
Keywords: International capital structure; dept.eco; dept.fin; pecking order theory; trade-off theory

The effects of noise and manipulation on the accuracy of collective decision rules - Bodo, Peter (2009)
How do noise and manipulation affect the accuracy of collective decision rules? This paper presents simulation results that measure the accuracy of ten well known collective decision rules under noise and manipulation. When noise is low these rules can be divided into accurate ("good") and inaccurate ("bad") groups. The bad rules' accuracy improves, sometimes significantly, when noise increases while the good rules' performance steadily worsens with noise. Also, when noise increases the accuracy of the good rules deteriorates at different rates. Manipulation delays the effects of noise: Accuracy improvement and deterioration due to noise emerge only at higher noise levels with manipulation than without it. In some cases at high noise levels there is only a negligible difference between the accuracy of good and bad collective decision rules. © 2009 Springer-Verlag Berlin Heidelberg.
Keywords: Accuracy Improvement; Acoustic noise; Collective decision; Collective decision rules; Decision theory; Fluorine containing polymers; Game theory; High noise levels; Higher noise levels; Manipulability; Manipulability of collective decisions; Noise sensitivity; Piezoelectric actuators; Simulation result; dept.eco

Economic liberalization and conditional volatility of exchange rate in sub-saharan africa: asymmetric GARCH analysis - Nandwa, Boaz; Andoh, Samuel K. (African Development Review-Revue Africaine De Developpement, 2008)
For small open economies, an understanding of movements in the exchange rate is imperative in analyzing trade and capital flows. In addition, reliable forecasting of exchange rate volatility is important in risk-taking assessment and investment decision-making, both of which are critical to long-term growth. Using an asymmetric GARCH-type approach, this paper examines the implications of economic liberalization on the stochastic behavior of the exchange rate series in a sample of sub-Sahara African (SSA) countries over the 1970-2004 period. The results indicate that exchange rate volatility is variable, and is less volatile under fixed exchange rate regime (pre-economic liberalization) and higher under flexible regime (post-economic liberalization), that is, it is asymmetric. For most of the countries, the EGARCH and TGARCH models are robust to parameter stability and gives better forecasting performance compared to the standard GARCH model.
Keywords: Africa; Sub-Saharan Africa; capital flow; decision making; dept.eco; exchange rate; forecasting method; investment; modeling; parameterization; stochasticity; trade flow; trade liberalization

Empirical relationship between macroeconomic volatility and stock returns: Evidence from Latin American markets - Abugri, Benjamin A (International Review of Financial Analysis, 2008)
Emerging market stock returns have been characterized as having higher volatility than returns in the more developed markets. But previous studies give little attention to the fundamentals driving the reported levels of volatility. This paper investigates whether dynamics in key macroeconomic indicators like exchange rates, interest rates, industrial production and money supply in four Latin American countries significantly explain market returns. The MSCI world index and the U.S. 3-month T-bill yield are also included to proxy the effects of global variables. Using a six-variable vector autoregressive (VAR) model, the study finds that the global factors are consistently significant in explaining returns in all the markets. The country variables are found to impact the markets at varying significance and magnitudes. These findings may have important implications for decision-making by investors and national policymakers. © 2006 Elsevier Inc. All rights reserved.
Keywords: Emerging markets; Latin America; Macroeconomic volatility; Stock returns; Vector autoregressive model; dept.eco; dept.fin

Predicting us 2001 recession, composite leading economic indicators, structural change and monetary policy - Mostaghimi, Mehdi (The Singapore Economic Review, 2006)
In an attempt to predict a peak in the US economy using a classical statistical decision methodology and a Bayesian methodology and using the 1996 revised composite leading economic indicators (CLI), it is learned that the Bayesian models have generally outperformed the classical statistical ones and, among the Bayesian models, the two using two and three consecutive CLI growth rates are superior in reliability and in accuracy. These two models, however, failed to correctly predict the 2001 recession. In investigating the reasons behind their failures, we learned that: (1) if the concurrent data for the economic structure of 1983-1999 are used for the prediction, they have also been able to predict the 2001 recession correctly, but their overall reliability is not as strong as before; (2) given the overwhelming weight of the monetary policy tools in the CLI-1996 design and the combination of the economic and political events in the year 2000, the less than expected effectiveness of the monetary policy since 2001 has contributed to this failure; and (3) a possible structural change in the US economy since 2000 has also contributed to this prediction failure. © World Scientific Publishing Company.
Keywords: Bayesian analysis; Bayesian probability forecasting; Classical statistical decision theory; Composite leading indicators; Information theory; Monetary policy; North America; Predicting recessions; Structural change; US economy; United States; dept.eco; economic analysis; economic conditions; economic structure; monetary policy; prediction; probability; structural change

Cost containment of total knee arthroplasty in the us: DWA analysis on regional cost and clinical comparison between 2010 and 2013 - Ball, Alexandra M.; Yu, Jia (Health, 2020)
Keywords: dept.eco; peer-reviewed

Genetically modified crops’ environmental impact and trust in eco-labels - Kwak, Lynn E.; Yoon, Sang Won; Kim, Younjun (Australasian Marketing Journal, 2020)
The U.S. Department of Agriculture expects companies to disclose genetically modified (GM) ingredients in foods and beverages by January 2022. While food companies fear that the stigma of GM labels could cause GM food sales to decline, eco-labeling could lessen the impact of GM-labeling. The results of the present research indicate that neither the eco-labeling alone nor the eco-labeling accompanied by information about the environmental benefits of GM crops influence consumers’ willingness to buy. Based on the mediation analysis, however, trust of eco-labels mediates the relationship between GM foods’ environmental friendliness information and consumers’ willingness to buy eco-labeled GM food. The theoretical and practical implications of the findings are discussed. © 2020
Keywords: Eco-labeling; Genetically modified (GM) foods; Trust; Willingness to buy; dept.eco; dept.mkt; peer-reviewed

‘Is it wise to open up America again now?’ Learning from government responses to COVID-19 and economy reopen points in three Asia-Pacific countries - Yu, Jia; Pang, Yulei (British Journal of Healthcare Management, 2020)
With the continuously increasing number of new confirmed COVID-19 cases, many health experts worried about the possibility of a ‘second wave’ outbreak, which might cause more deaths and hit economies even worse. This article looks at the experiences of fighting COVID-19 from three Asia-Pacific countries and discusses whether it is a wise decision to open up America again at this time.
Keywords: dept.eco; dept.mat; peer-reviewed

Cohabitation before marriage? An examination of pre-acquisition alliance partnerships and merger outcomes - Yu, Han; He, Zhaozhao (Review of Quantitative Finance and Accounting, 2019)
Keywords: dept.eco; peer-reviewed

MADness in the method: On the volatility and irregularity of technology diffusion - Bodo, Peter (Technological Forecasting and Social Change, 2016)
The paper investigates how some drivers of technology diffusion shape the volatility and irregularity of the diffusion process. It presents an agent-based simulation model of technology diffusion that includes variables to control technology generations, social pressures, market size, and network randomness. Several variable combinations are defined, technology diffusions are simulated, and the volatility and irregularity of the process are measured. The paper explores scenarios with unusually high volatility and/or irregularity in more detail. It shows that technology generations mostly affect volatility, social pressures impact irregularity, while network randomness and market size amplify the other two factors' effects. Also, the paper argues that market structure changes generated by the factor combinations in question indirectly affect diffusion volatility and irregularity and these indirect effects may explain very high levels of, and unexpected changes in the volatility and irregularity of the technology diffusion process. (C) 2016 Elsevier Inc All.rights reserved.
Keywords: Agent-based model; Agent-based models; Agent-based simulation models; Autonomous agents; Brand and product category competition; Commerce; Computational methods; Control technologies; Diffusion; Diffusion process; Economic and social effects; Market structures; Network randomness; Product categories; Random processes; Several variables; Technology diffusion; Technology generations; competition (economics); dept.eco; network analysis; numerical model; technology diffusion

Ownership structure, non-interest income and bank risk in ghana - Abugri, Benjamin A; Osah, Theophilus Teye; Andoh, Samuel (Banking and Finance Review, 2016)
This study investigates the relationship between bank ownership structure, non-interest income and risk in an emerging market setting. Our analysis shows that the relationship between product diversification and bank risk is significantly influenced by asset size and ownership structure. In contrast to large banks, small banks are exposed to higher risk when the income share of non-traditional banking activities rise. We also find strong evidence of differences in risk exposure of banks to non-interest income after controlling for ownership structure. Private domestic and private foreign banks experience lower risk with higher non-interest income while the converse is true for public domestic banks. Furthermore, we show that the speed with which risk adjust to non-income activities is faster for domestic private banks than for foreign banks. These results could provide useful information to investors and regulators of banking institutions as they seek to reconcile the important issues of bank ownership structure, income diversification and size on the one hand with the level of risk exposure on the other hand. © 2016, Banking and Finance Review.
Keywords: Bank risk; Ghana; Non-interest income; Ownership structure; dept.eco; dept.fin; ⛔ No DOI found

Sustainable growth with irreversible stock effects of renewable resources - Lopez, Ramon; Yoon, Sang Won (Economics Letters, 2016)
This paper examines sustainability conditions when the stock effects of renewable resources prevail, and characterizes the maximal critical level of initial pollution emissions such that Pigovian tax alone ensures sustainable growth. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Optimal pollution tax; Renewable resources; Stock effects; Sustainable growth; dept.eco

Is current trade pattern between the developed and developing countries environmentally sustainable - Yoon, Sang Won (International Journal of Economics and Finance, 2016)
Keywords: dept.eco

Oiling the urban economy: land, labour, capital, and the state in Sekondi-Takoradi, ghana, written byFranklin obeng-odoom - Andoh, Samuel K. (African and Asian Studies, 2015)
Keywords: dept.eco; peer-reviewed

Real exchange rates in advanced transition economies - Grubacic, Sanja; Schuster, Julian (Journal of Eastern European and Central Asian Research (JEECAR), 2015)
The recent evidence from Eastern Europe suggests that one of the major obstacles towards the adoption of euro may lie in the impact that the recession of 2008 exerted on the trajectory of real exchange rates in new member countries (European Commission, 2015). This paper aims to establish and explain the relationship between the external shocks derived from the global financial crisis and recession of 2008 and equilibrium real exchange rate in advanced transition economies of Eastern Europe. The interplay between the external and internal balances is explained by developing an inter-temporal optimizing model of the real exchange rate determination in a small open economy with structural distortions. The results of our model suggest that, in the aftermath of recession, if the Eastern European economies attempt to restore and maintain the balance between the consumption, saving, and investment, the equilibrium real exchange rate will tend to reverse its trajectory from appreciation to depreciation over time in order to encourage a greater production in the future. The equilibrium real exchange rate depreciation in the future may obtain either as a result of an increase in the direct subsidies on investment or as a result of reduced subsidies on the "net-of-investment" income. The deprecation of countries’ real exchange rate, however, may continue to act as an effective constraint against the adoption of euro. © 2015, Institute of Eastern Europe and Central Asia. All rights reserved.
Keywords: Eastern European countries; Real exchange rates; Recession; Subsidies; Transition; dept.eco

Regulation of transportation network companies: A case study of connecticut - Thorson, James A (NABET 2015 Faculty Conference, 2015)
Keywords: dept.eco; ⛔ No DOI found

Book Review: armenia and azerbaijan through peace and war: black garden: 10 year anniversary edition, written by thomas de waal - Andoh, Samuel K (African and Asian Studies, 2014)
Keywords: book.review; dept.eco; peer-reviewed

Zimbabwe's land reform: myths and realities (review) - Andoh, Samuel K (Africa Today, 2011)
Keywords: dept.eco

Land, power, and custom: controversies generated by south africa's communal land rights act - Andoh, Samuel K (Africa Today, 2010)
Keywords: dept.eco

Small loans, big dreams: how the nobel prize winner muhammad yunus and microfinance are changing the world, edited by alex counts - Gebremariam, Yilma (Eastern Economic Journal, 2010)
Keywords: dept.eco

Attention on adolescent mental disorders: the long-term effects on labor market outcomes - Yu, Jia (International Journal of Applied Economics, 2019)
According to a presidential task force about national college health in 2005, 14.9% of college students have been diagnosed with depression or anxiety disorders. Almost 75% of them experienced mental health problems during their early childhood or adolescence. Specifically, this paper examines the longitudinal effects of learning disability and attention disorder, and behavior disorder, of children born in 1980 – 1984, on their labor market outcomes as young adults. This study applies data from the National Longitudinal Survey of Youth 1997 (NLSY97), which documents the transition from school to work, and from adolescence to adulthood. By applying a family fixed effects model with Heckman selection procedure and multinomial logistic regression, the research results show that experiencing mental health illness during childhood is associated with a decreased risk of employment, an increased risk of unemployment, and decreased weekly paid working hours. This effect is strong and significant for males, and barely discernible for females. Hence, childhood mental disorder is an important determinant of individual’s labor market outcomes. Targeting the improvement for boys’ mental illness situation might be beneficial for improving their labor market participation.
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Sustainable development: Structural transformation and the consumer demand - López, Ramón E.; Yoon, Sang W. (Structural Change and Economic Dynamics, 2020)
This paper examines the feasibility of environmentally sustainable growth in a competitive market economy assuming various types of technological changes affecting pollution emissions and ultimately climate change. We consider two final outputs and two factors of production, accounting for both pollution flow and stock effects. If the initial level of pollution emissions satisfies certain boundary conditions, a Pigouvian pollution tax may assure sustainable growth without any further government intervention. This is true even if exogenous technological change is assumed to benefit exclusively the pollution-intensive industries (the “dirty” sector). A consumers’ composition effect (often neglected in the literature), driven by an endogenous change in the relative prices between clean and dirty final goods under an optimal pollution tax, plays a critical role in the structural transformation process to achieve long-run sustainable economic growth.
Keywords: Consumption flexibility; Optimal pollution tax; Sustainable development; Technological change; boundary condition; dept.eco; economic growth; emission; environmental economics; pollution tax; sustainable development; technological change

ICT and transport infrastructure development: an empirical analysis of complementarity - Na, Kyoung Y.; Kim, Dong H.; Park, Byoung G.; Yoon, Sang W.; Yoon, Chang-Ho (Applied Economics, 2020)
This paper provides an empirical framework to assess the nonlinear complementary linkage effects that arise from the interaction between motorway capital and information and communications technology (ICT) capital in developed economies. Using panel data from the Organisation for Economic Co-operation and Development (OECD) member countries and controlling for endogeneity, the paper finds that there exists a critical mass for ICT capital such that if the capital grows beyond the critical mass, the marginal contribution of motorway capital to productivity growth increases as the motorway is extended. This empirical result explains variations in the productivity contributions of transport infrastructure across countries that differ in their ICT infrastructure and has implications for setting the investment priorities of key components of infrastructure. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: ICT capital; OECD; complementarity; dept.eco; empirical analysis; information and communication technology; infrastructural development; infrastructure development; motorway; panel data; peer-reviewed; productivity; productivity growth; transportation infrastructure

Are hedge fund returns affected by media coverage of macroeconomic news? - Dutta, Sandip; Thorson, James (Studies in Economics and Finance, 2019)
Purpose: Extant literature suggests that the difficulty associated with the interpretation of macroeconomic news announcements by the market in general in different economic environments, might be the reason why most studies do not find any significant relationship between real-sector macroeconomic variables and financial asset returns. This paper aims to use a different approach to measure macroeconomic news. The objective is to examine if a different measure of a macroeconomic news variable, constructed from media coverage of the same, significantly affects hedge fund returns. Design/methodology/approach: The authors use a news index for unemployment, which is a real-sector variable, constructed from newspaper coverage of unemployment announcements and examine its impact on hedge fund returns. Findings: Contrary to the other studies that examine the impact of macroeconomic news on hedge fund returns, the authors find that media coverage of unemployment news announcements significantly affects hedge fund returns. Practical implications: Overall, this paper demonstrates that the manner in which the market interprets macroeconomic news announcements in different economic environments is probably a more relevant factor for hedge funds and is more likely to impact hedge fund returns. In conjunction with variables – constructed from media coverage of unemployment news announcements – that factor in the manner of interpretation, it is found that surprises also matter for hedge fund returns. This is an important consideration for hedge fund managers as well. Originality/value: To the best of the authors’ knowledge, this is the first study that examines the impact of media coverage of macroeconomic news announcements on hedge fund returns and finds significantly different results with real-sector macro variables. © 2019, Emerald Publishing Limited.
Keywords: Finance; Financial economics; dept.eco; dept.fin; peer-reviewed

Estimation of a production function for Philippine retail stores - Patalinghug, Jason C. (Economics, 2019)
Abstract The purpose of this paper is the estimation of a production function for retail stores in the Philippines. A generalized Cobb-Douglas production function is utilized for this purpose. Ordinary Least Squares is used in obtaining the coefficients for labor and capital. The results show that the marginal product of labor to be higher than the marginal product of capital and the hypothesis of constant returns to scale is not rejected.
Keywords: dept.eco; peer-reviewed

The intra-industry effects of proxy contests - Chen, Fang; Huang, Jian; Yu, Han (Journal of Economics and Finance, 2020)
In this study, we examine the intra-industry effect of proxy contests. Proxy contests convey the information of common industrial risks or expected competitive relationship change. We find significant negative abnormal returns in the group of competitors of target firms with negative abnormal returns, and such negative abnormal returns become larger for similar-size competitors. In contrast, there are no significant abnormal returns for competitors of target firms with positive abnormal returns. These findings are consistent with the information-based theory but not the competitive theory. © 2019, Academy of Economics and Finance.
Keywords: Competitive effect; Information-based effect; Intra-industry effect; Proxy contest; dept.eco; dept.fin; peer-reviewed

Pre-play learning and the preference reversal phenomenon - Kim, Younjun; Hoffman, Elizabeth (Southern Economic Journal, 2018)
Elicited preference rankings for two lotteries are typically inconsistent across choice and pricing tasks. We test whether pre-play learning makes preference rankings consistent. Pre-play learning denotes ex-ante lottery learning, where subjects observe playing lotteries before making decisions. We find that pre-play learning makes the average selling prices for the p-bet, of subjects who choose the p-bet, higher than their average selling prices for the $-bet. However, pre-play learning is not strong enough to equalize the rates of standard and non-standard reversals, although pre-play learning reduces the rate of standard reversals.
Keywords: C91; D12; D81; dept.eco; peer-reviewed

Emission tax and market power - Yoon, Sang Won (Atlantic Economic Journal, 2018)
Keywords: L13; Q00; dept.eco; peer-reviewed

Firm risk and proxy fights: Evidence from SOX - Chen, Fang; Huang, Jian; Yu, Han (Accounting and Finance Research, 2018)
The Sarbanes Oxley Act of 2002 (SOX) is documented to curb executive risk-taking and firm risk. Utilizing SOX as an exogenous shock on firm risk, we find that proxy fight threats are positively related to a firm’s total risk and idiosyncratic risk. Specifically, although firm risk generally decreases post-SOX, high proxy fight threats mitigate this change in firm risk. We also find that although firms adopt more conservative policies such as decreasing their leverage and payout post-SOX, these changes are mitigated by proxy fight threats. In sum, our findings indicate that proxy fights act as an external disciplinary mechanism, encourage executive risk-taking, and increase firm risk.
Keywords: dept.eco; dept.fin; peer-reviewed

Inflation targeting and monetary policy rules - Patalinghug, Jason C. (Global Economic Observer, 2018)
This paper examines the literature to try to explain the concept of inflation targeting. There are at present two competing monetary policy rules: (1) targeting rules and (2) instrument rules. The objective of this paper is to review the relative merits of these two monetary policy rules. The debate between using either an inflation targeting rule or an instrument rule debate displays the lack of consensus among economists concerning the proper specification and underlying assumptions of the inflation-targeting model which is suited for the analysis of key monetary policy issues. The paper also examines what recent studies have found about the effect of inflation targeting on emerging markets. These studies have shown that inflation targeting has been largely beneficial to emerging markets.
Keywords: Central Bank; Instrument Rules; Macroeconomics; dept.eco; peer-reviewed; ⛔ No DOI found

On the impossibility of sustainable growth in a manufacturing based economy - Yoon, Sang Won; Yoon, Chang-Ho (Economic Research-Ekonomska Istraživanja, 2018)
This paper investigates a possibility of sustainable growth in a multi-output endogenous growth framework where the capital accumulation takes place mainly through the production of the dirty manufactured goods. It is shown that in a closed economy, economic growth is not environmentally sustainable, even under an optimal pollution tax unless the consumption elasticity of substitution between clean and dirty goods approaches infinity as in a small open economy which exports dirty goods. There exists a minimal threshold level of the ratio of clean to dirty capital that ensures sustainable growth in a closed economy.
Keywords: Kuznets curve; Sustainable growth; consumption behavior; dept.eco; economic growth; elasticity; elasticity of marginal utility; elasticity of substitution; environmental Kuznets curve; peer-reviewed; sustainable development

Africa’s natural resources and underdevelopment: how Ghana’s petroleum can create sustainable economic prosperity, written by Kwamina Panford, (2016) - Andoh, Samuel K (African and Asian Studies, 2018)
Keywords: dept.eco; peer-reviewed

Economic nationalism in the history of international economics - Grubacic, Sanja; Schuster, Julian (International Journal of Pluralism and Economics Education, 2018)
This paper examines the sources of economic nationalism by a closer examination of the theory and policy of international trade, originating in the 19th century. We compare and contrast the views of British classical writers, the main proponents of trade liberalism, with the writings of Friedrich List, the main proponent of economic nationalism. The focus is on the distributional implications of trade, and the treatment of the benefits that a poor country may derive from trading with a rich country in 19th century economic thought. We also review the current literature on economic nationalism, and find that alternative perspectives emerge from differing views on the benefits and drawbacks of globalisation. We argue that List's approach remains relevant to understanding contemporary economic nationalism because it highlights a historical context in which the adverse distributional implications of foreign trade are likely to provoke nationalist sentiment. © 2018 Inderscience Enterprises Ltd.
Keywords: Distribution; Economic liberalism; Economic nationalism; Free trade; Globalisation; History; Inequality; International economics; List; Malthus; Protectionism; Ricardo; dept.eco; peer-reviewed

Stale economic news, media and the stock market - Birz, Gene (Journal of Economic Psychology, 2017)
I employ a classification of headlines from newspapers and wire services to examine whether stale macroeconomic news affects stock prices. Unlike with individual stocks, the cost of obtaining information about major economic releases is relatively low. Thus, stock prices should adjust to economic news announcements prior to their coverage in newspapers. I find statistically and economically significant relationship between stale news stories on unemployment and next week's S&P 500 returns. This effect is then completely reversed during the following week. These findings show that investors are affected by salient information and support the hypothesis that investors overreact to stale macroeconomic news reported in newspapers. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Attention; Efficient markets; Macroeconomic announcements; Media; Salience; dept.eco; dept.fin

Classical literature gives life to business paradox and systems integration - Page, Robert; Andoh, Samuel; Smith, Robert (Administrative Issues Journal Education Practice and Research, 2017)
Keywords: dept.eco; dept.mgt

What does improved spectrum management mean for the Philippines? - Patalinghug, Epictetus; Patalinghug, Jason (Annals of the Constantin Brancusi University of Targu Jiu, Economy Series, 2019)
This paper analyzes spectrum management practices in the Philippines. The regulatory body allocates available spectrum via an administrative approach which lacks transparency and due process. The paper recommends that the regulatory body adopts the auction method in allocating spectrums which is more transparent, fair, and cost-effective if a suitable design is adopted.
Keywords: Allocation Methods; Auction; Philippines; Spectrum Management; dept.eco; ⛔ No DOI found

An investigation into the sensitivity of money demand to interest rates in the Philippines - Patalinghug, Jason C. (Journal of Applied Business and Economics, 2017)
A scholarly article by author Jason C. Patalinghug, published in the Journal of Applied Business and Economics
Keywords: dept.eco; ⛔ No DOI found

Examining the dynamic linkages of performance and volatility of REIT returns - Dania, Akash; Dutta, Sandip (The Journal of Wealth Management, 2017)
This article extends the literature on the financial performance of real estate investment trusts (REITs) by examining whether U.S. REIT returns are impacted by global REITs and other real estate subsectors, such as the U.S. Real Estate Index (USRE) and the U.S. Mortgage Finance Index (USMF). The authors also explore the issue of volatility transmission and the asymmetric effect of volatility spillover on U.S. REIT returns from innovations originating in other real estate subsectors and Global REITs. Results suggest that U.S. REITs are impacted by USRE and USMF returns. There is also evidence of volatility spillover from key real estate constituents-that is, USRE and USFM returns and global REIT markets. These results can be attributed to the changing dynamics of the real estate sector and the gradual integration of the global real estate sector as an asset class. These findings have strong implications for constructing global portfolios including REITs.
Keywords: dept.eco; dept.fin

Broadband internet and new firm location decisions in rural areas - Kim, Younjun; Orazem, Peter F. (American Journal of Agricultural Economics, 2017)
Keywords: dept.eco; peer-reviewed

Universal demographic data collection standardization for better decision-making - Yahav, Lara; Thorson, James (American Journal of Management, 2017)
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Comparison of Single-Payer and Non Single-Payer Health Care Systems: A Study of Health Administration Efficiency - Yu, Jia; Zhang, Yi (Modern Economy, 2017)
The United States spends nearly twice as much per capita on health care as several OECD countries. Based on previous research, universal health care decreases the total health care expenditure due to the single-payer system; it is still unknown whether a mixed health care system has superiority. In this study, we compare and evaluate both quality of care and administrative costs among six developed countries, upon three groups: single-payer universal health care system (Australia and Canada), two-tier health care system (France and Japan), and insurance mandate health care system (Switzerland and the US). The results show that both single-payer system and two-tier system are superior to insurance mandate system on health insurance administration costs. Also, regarding insurance mandate system, the healthcare system in Switzerland is more efficient than that in the US. So, we conclude that it is possible for the US to choose a diverse healthcare system, instead of focusing on one system, to trim the healthcare administration cost and improve the quality of care for the entire country.
Keywords: dept.eco

A comparative analysis of Ethiopian and Ghanaian women entrepreneurs - Thorson, James; Gebremariam, Yilma; Andoh, Samuel K. (International Journal of Interdisciplinary Research, 2017)
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found